Mathematical Analysis of Alternative Power Systems in a Northern Wisconsin Home - Hannah LeMoine; Sicheng Mo; Yuchi Dong; Wufeng Tian (Journal of Energy Conservation, 2019)
The effects of global warming have been causing irreversible damage to the Earth over the past decades. One way we can reduce our individual impact on the environment is to focus on the production and consumption of Eco‐friendly sources of electricity such as solar, wind, or bio-electric energy. Based on the current available and suitable energy options, we have proposed to modify a chosen house from Northern Wisconsin by using a hybrid system including solar energy and wind turbine energy to replace the traditional power grid. Considering sunlight‐time, wind speed in Northern Wisconsin, we have predicted the immediate and long‐term fiscal and environmental impacts. From this cost‐benefit analysis, we project that the best hybrid option is a combination of 95% solar power and 5% wind energy, which would save about 41,000 over the next 30 years.
Keywords: Renewable Energy